2011
DOI: 10.3389/fmicb.2011.00018
|View full text |Cite
|
Sign up to set email alerts
|

Asc-Dependent and Independent Mechanisms Contribute to Restriction of Legionella Pneumophila Infection in Murine Macrophages

Abstract: The apoptosis-associated speck-like protein containing a caspase recruitment domain (Asc) is an adaptor molecule that mediates inflammatory and apoptotic signals. Legionella pneumophila is an intracellular bacterium and the causative agent of Legionnaire's pneumonia. L. pneumophila is able to cause pneumonia in immuno-compromised humans but not in most inbred mice. Murine macrophages that lack the ability to activate caspase-1, such as caspase-1−/− and Nlrc4−/− allow L. pneumophila infection. This permissivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 67 publications
0
52
0
1
Order By: Relevance
“…A recent complementary work 21 showed that infection of macrophages with Francisella tularensis initiated AIM2-dependent apoptosis in caspase-1-knockout cells. Another recent work has shown ASC-dependent cleavage of caspase-3 in response to NLRC4 inflammasome activation by Legionella pneumophila, 37 and in a separate study, apoptosis was induced by inflammasome responses to Salmonella enterica in Casp1 À / À cells. 38 Thus inflammasomedependent apoptosis is relevant to infectious agents.…”
Section: Discussionmentioning
confidence: 82%
“…A recent complementary work 21 showed that infection of macrophages with Francisella tularensis initiated AIM2-dependent apoptosis in caspase-1-knockout cells. Another recent work has shown ASC-dependent cleavage of caspase-3 in response to NLRC4 inflammasome activation by Legionella pneumophila, 37 and in a separate study, apoptosis was induced by inflammasome responses to Salmonella enterica in Casp1 À / À cells. 38 Thus inflammasomedependent apoptosis is relevant to infectious agents.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, Pierini et al showed that apoptotic responses triggered through AIM2 inflammasome activation may be involved in macrophage cell death induced by Francisella tularensis (71). Another study demonstrated that in murine macrophages, NLRC4-and ASC-dependent cleavage of procaspase-3 generates functional executioner caspase-3 in response to Legionella pneumophila infection (72). Furthermore, Sagulenko et al suggested that the activation of AIM2 and NLRP3 inflammasomes induces both apoptotic and pyroptotic cell death pathways, leading to the activation of the executioner caspases, caspase-8 and caspase-3 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Because the Western blot technique of IL-1b p17 detection appeared to be less sensitive than the ELISA, IL-1b secretion was measured by ELISA 24 h poststimulation with L. interrogans at the MOI of 100 in all subsequent experiments. To find out the inflammasome protein involved in the secretion of IL-1b by BMDMs infected with L. interrogans, we first tested the contribution of ASC, the adaptor of inflammasomes, important for cytokine secretion (19). In contrast to IL-6 secretion that was comparable in L. interrogans-stimulated wild-type (WT) and ASC-deficient BMDMs, IL-1b secretion upon L. interrogans infection or stimulation with heat-killed bacteria was almost abrogated in ASCdeficient BMDMs compared with WT BMDMs (Fig.…”
Section: Interrogans Infection Induces Il-1b Secretion Through Nlrmentioning
confidence: 99%